Verification of Performance in Results-Based Financing : The Case of Afghanistan - World Bank Group (World Bank, Washington, DC, 2016)
Since the end of the Taliban period, Afghanistan made remarkable progress, particularly in the health sector. Between 1990 and 2013, infant mortality declined from 121.3 to 70.2 deaths per 1’000 live births; under 5 mortality diminished from 179.1 to 97.3 deaths per 1’000 live births; and maternal mortality dropped from 1’300 to 460 maternal deaths per 100’000 live births. To further improve the coverage and utilization of Maternal and Child Health (MCH) services, the Government of Afghanistan – under the stewardship of the Ministry of Public Health (MOPH) – launched a new supply-side Results-Based Financing (RBF) scheme, covering 11 provinces and providing a standardized basic package of health services (BPHS). This package focuses on priority MCH services such as antenatal care (ANC), post-natal care (PNC), delivery care, nutrition, immunization coverage, tuberculosis (TB), as well as quality of care. This RBF program contracts international NGOs, incentivizing them for both the quantity and the quality of select services.